On the performance of a novel dressing tool with controlled geometry and density of abrasive grits. Issue 1 (2017) - Spampinato, Alessio; Axinte, Dragos; Butler-Smith, Paul; Novovic, Donka
Abstract: This paper reports on an innovative rotary dresser, characterised by abrasive features with controlled geometries and spatial arrangements. The performance of the novel dresser has been evaluated against conventional dressers (random and handset grit distributions) in terms of output forces and wear of the abrasives supported by electron scanning microscopy and metrological investigations. The proposed dresser showed improved wear resistance and significant (50%) reduction of radial forces when compared with conventional tools. This novel approach opens the possibility to vary density of abrasives to obtain uniform wear rates for complex geometry tools while allowing easy restoration of their abrasive properties.